2018
DOI: 10.1039/c8cc02855a
|View full text |Cite
|
Sign up to set email alerts
|

A live bacteria SERS platform for the in situ monitoring of nitric oxide release from a single MRSA

Abstract: A simple and unique surface-enhanced Raman spectroscopy (SERS) platform is developed for the precise and sensitive in situ monitoring of nitric oxide (NO) release from an individual bacterium. Using this live bacteria SERS platform, NO release from MRSA under the stress of antibiotics and co-infected bacteria was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…A simple and novel SERS platform is fabricated for in situ monitoring the nitric oxide (NO) release of a single bacterium. NO released under antibiotics and co-infected bacteria stress was investigated using this method [ 153 ]. Staphylococcal Enterotoxin B (SEB) was detected ultrasensitively using the SRES sandwich immunoassay.…”
Section: Application On the Detection Of Microorganism Original Bimentioning
confidence: 99%
“…A simple and novel SERS platform is fabricated for in situ monitoring the nitric oxide (NO) release of a single bacterium. NO released under antibiotics and co-infected bacteria stress was investigated using this method [ 153 ]. Staphylococcal Enterotoxin B (SEB) was detected ultrasensitively using the SRES sandwich immunoassay.…”
Section: Application On the Detection Of Microorganism Original Bimentioning
confidence: 99%
“…A ratiometric SERS probe based on immobilizing 3,4-diaminobenzene-thiol onto trisoctahedral gold nanostructures has been successfully developed for real-time monitoring and imaging of trace NO in live cells [ 189 ]. Then monitoring of NO released from an individual bacterium in situ has been successfully realized adopting plasmonic nanostructure-based live bacteria as SERS platform [ 190 ]. Recent research reported a molecular probe based on bodipy that can systematically provide temporal information on NO by fluorescence imaging and SERS fingerprinting [ 191 ].…”
Section: Sers Applications In the Detection Of Effector Moleculesmentioning
confidence: 99%
“…SERS refers to a phenomenon of Raman scattering signal enhancement caused by the adsorption of certain molecules on the surface of nano-sized rough metal 1113 . Combining the high selectivity of the aptamer reaction with the highly sensitive SERS is a major innovation in nanoplasma, which has achieved good results.…”
Section: Introductionmentioning
confidence: 99%